การฟื้นฟูภาวะจิตใจและการร่วมมือช่วยเหลือทางจิตวิทยาที่ยั่งยืนแก่เด็ก เยาวชนและครอบครัวหลังการประสบภัยพิบัติสึนามิ : รายงานวิจัยฉบับสมบูรณ์ - พรรณทิพย์ ศิริวรรณบุศย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This study was constructed to propose the sustainable mental rehabilitation and collaborative psychological rebuilding for children, adolescent, families and teachers. Three phases of the long term research plan are : Phase 1, conduct a needs assessment of children, adolescent, families and teachers; Phase 2. Examine the impacts of the tsunami on the daily lives of children, adolescent, families and teachers; Phase 3, propose a rehabilitation center to implement and monitoring community outreach and support for children, adolescent, families and teachers. Subjects consisted of four groups of 240 elementary student and 226 secondary school students, 187 family menders, and 128 teachers in Phang Nga Province. Three survey forms were conducted : needs assessment, impacts of tsunami and a self-care behaviors. Results of phase 1 and phase 2 indicated that; Phase 1 : needs assessment for each group: the highest score of children was the need for new family for the tsunami victim; the highest score of adolescents was the need of scholarships for further education; the highest score of teacher was the need for sustainable rehabilitation of psychological rebuilding Phase 2: Impact of the Tsunami : physical and cognitive abilities impacted on all groups of children with tsunami exposure but emotional development impacted only children aged 11-12 ; adolescents who experienced high impact from tsunami were likely to develop emotional and behavioral problems than those who had no or little impact; the highest score of impact from tsunami for families of victims was family functioning ; physical, emotional and family’s problems impacted teachers. Phase 3: Two conference meetings were arranged to assure that the findings of research project reach out key stakeholders. Community leaders health care professional, school teachers, medias, and paraprofessional reported satisfying outcomes. In particular, prolong engagement of the project in the tsunami impact areas and community involvement in the process of dissemination the result were mentioned as the most profits. Most stakeholders suggested setting up a psychological and mental health services center for tsunami survivors. This center should be based on active collaboration between local and national related agencies. Through the center, community members will become familiar with psychological and mental health professionals in the region that can be accessed for referrals and outreach services.